MANAJEMEN KONFLIK DALAM TIM PELAYANAN KEBIDANAN: STUDI KASUS DAN STRATEGI PENYELESAIAN - Sri Rahma Friani; Meli Safreni Turnip; Adventides Natali Siahaan (Politeknik Ganesha Medan, 2022)
The midwifery care team, comprised of various professionals such as midwives, doctors, nurses, and other support staff, is a crucial unit in providing maternal and child health care. However, diverse backgrounds, experiences, perceptions, and high work pressure often trigger conflict. Poorly managed conflict can negatively impact team communication, staff job satisfaction, and, most importantly, patient quality and safety. This literature review aims to explore common sources of conflict within midwifery care teams, analyze their impact, and identify effective conflict management strategies. The review indicates that intrapersonal, interpersonal, and interprofessional conflict often arise from differences in role perceptions, time pressure, workload, and communication styles. The most effective conflict resolution strategies involve open communication, mediation, collaboration, and the development of negotiation skills. Successful implementation requires strong leadership to create a supportive team culture that promotes dialogue and is oriented toward problem-solving.